Medieval Legacy in the Poetry of Ivan V. Lalić - Prgomelja, Marija J. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Ivan V. Lalić has entered the Serbian literature in a big way in the mid-fifties, concentrating on the most important issues of poetry and form, related to the role of tradition and culture in writing. In his poetics, he united the traditional and modern, „a duality of visible and invisible”, united the Catholic and the Orthodox notions of the Virgin Mary, unified the experience of centuries past, emphasizing the principle of measure and spiced up all that with a Mediterranean vibe, linking his poetry to the language and heritage of his people, thus delineating basic symbols of national culture, speaking from the depths of the collective memory. His horizons and fields of poetry were established on the heritage of Christianity and the Byzantine patrimony, and promote the synthesis of medieval and modern poetry. Here we study the reflexes of medieval literature in the collections Passionate measures, Acts of love or Byzantium, Letter, Four Canons, the modification of medieval motifs and forms that exist in the collections. The last collection called Four Canons, on which Lalić worked for over twenty years, is the culmination of his creativity,the pinnacle of his poetic artistry, since the canon, the most prestigious form of religious poetry, moves from clerical to artistic poetry.